Crystal structure of the potassium channel KirBac1.1 in the closed state. - Kuo, A; Gulbis, J; Antcliff, J; Rahman, T; Lowe, E; Zimmer, J; Cuthbertson, J; Ashcroft, F; Ezaki, T; Doyle, D (2003)
The KirBac1.1 channel belongs to the inward-rectifier family of potassium channels. Here we report the structure of the entire prokaryotic Kir channel assembly, in the closed state, refined to a resolution of 3.65 angstroms. We identify the main activation gate and structural elements involved in gating. On the basis of structural evidence presented here, we suggest that gating involves coupling between the intracellular and membrane domains. This further suggests that initiation of gating by membrane or intracellular signals represents different entry points to a common mechanistic pathway.